Community mediation in Malaysia and IIAM community mediation service: a comparative study / Hanna Ambaras Khan - Ambaras Khan, Hanna; Abdul Hak, Nora; Ambaras Khan, Mushera (2014)
Community Mediation programme in Malaysia is a Government effort through Department of National Unity and Integration ("DNUI") in providing a channel to settle disputes or problems at the community level through mediation process. The programme is still young and there are many rooms for improvement. On the other hand, the Indian Institute of Arbitration and Mediation ("IIAM") Community Mediation Service is a product of IIAM, a private institution in Cochin, Kerala. The institute has taken a great effort to provide mediation services for the people to settle their disputes. The mediation‟s processes are conducted by mediators at Mediation Clinics. IIAM has developed a mechanism in handling the Mediation Clinic that is financially and administratively independent from government. Malaysia may learn some lessons from IIAM to improve the current community mediation programme especially in term of funding. The objective of this paper is to compare the practice of both countries in administrating community mediation programme and to make suggestions to DNUI in improving the current programme.